A catalogue of type material of the British Diapria genus group (Hymenoptera, Proctotrupoidea, Diapriidae). - Notton, David G. (Contributions to Entomology = Beiträge zur Entomologie, 1995)
Type material of all British species of the Diapria group (Diapria, Tetramopria, Trichopria and Viennopria) is catalogued. Material seen includes 19 holotypes and 45 lectotypes of which 41 are designated. Type material of Diapria verticillata Latreille, D. nigra Nees, D. picicornis Nees, D. carinata Thomson, D. basalis Thomson, Loxotropa nigricornis Marshall, Diapria apicalis Kieffer, D. myrmecobia Kieffer, D. stilata Kieffer, Trichopria atricornis Kieffer, T. evanescens Kieffer, T. natans Kieffer and T. elegans Priesner is regarded as lost. Type material of Diapria modesta is regarded as destroyed and a neotype is designated. Two new names are proposed as follows: Trichopria nixoni nom. nov. for T. bifoveata Nixon preocc.; Trichopria paludicola nom. nov. for T. nana Nixon preocc. Four new combinations are proposed: Diapria modesta Ratzeburg and Diapria ruficornis Thomson are transferred to Trichopria; Trichopria natans Kieffer and Trichopria elegans Priesner are transferred to Viennopria. Thirty new synonyms are proposed: Diapria nigricornis Thomson = D. elongata Thomson; Trichopria aequata (Thomson) = T. carinata (Thomson), = T. petiolata (Thomson), = T. isis Nixon; T. basalis Thomson = T. thomsoni Kieffer, = T. ciliaris Kieffer; T. cameroni (Kieffer) = T. minima (Masi); T. credne Nixon = T. stelenes Nixon; T. fucicola (Walker) = T. longiclava (Masi), = T. miron (Nixon); T. halterata (Kieffer) = T. atricornis Kieffer, = T. morleii (Chitty in Morley), = T. brachyptera Maneval, = T. balli Maneval; T. hyalinipennis (Thomson) = T. tetratoma (Kieffer), = T. oxygaster Masner; T. incrassata (Jansson) = T. alifera Nixon; T. modesta (Ratzeburg) = T. longicornis (Thomson), = T. sociata (Kieffer); T. nigra (Nees) = T. ruficornis (Thomson), = T. fimbriata Kieffer; T. nigricornis (Marshall) = T. laticeps (Kieffer), = T. thomsoni (Kieffer); T. oogaster (Thomson) = T. nigripes (Thomson); T. prema Nixon = T. debauchei Wall; T. subimpressa (Kieffer) = T. clavatipes (Kieffer), = T. sequester Nixon; T. suspecta (Nees) = T. picicornis (Nees) and Viennopria lacustris (Schulz) = V. natans (Kieffer), = V. elegans (Priesner). A British checklist of 36 currently recognised species in four genera is given. Nomenclatural Acts aequata Thomson, 1858 (Diapria), Lectotype; syn. n. of Trichopria carinata (Thomson, 1858) elongata Thomson, 1858 (Diapria), Lectotype; syn. n. of Diapria nigricornis Thomson, 1858 longicornis Thomson, 1858 (Diapria), Lectotype; syn. n. of Trichopria modesta (Ratzeburg, 1848) nigricornis Thomson, 1858 (Diapria), Lectotype nigripes Thomson, 1858 (Diapria), Lectotype; syn. n. of Trichopria oogaster (Thomson, 1858) petiolata Thomson, 1858 (Diapria), Lectotype; syn. n. of Trichopria aequata (Thomson, 1858) picicornis Nees, 1834 (Diapria), syn. n. of Trichopria suspecta (Nees, 1834) ruficornis Thomson, 1858 (Diapria), Lectotype; syn. n. of Trichopria nigra (Nees, 1834) clavatipes Kieffer, 1911 (Diapria (Tropidopria)), Lectotype; syn. n. of Trichopria subimpressa (Kieffer, 1911) inaequalis Kieffer, 1911 (Diapria (Tropidopria)), Lectotype now a synonym of Trichopria aequata (Thomson, 1858) melanopa Kieffer, 1911 (Diapria (Tropidopria)), Lectotype now a synonym of Trichopria subimpressa (Kieffer, 1911) nocticolor Kieffer, 1911 (Diapria (Tropidopria)), Lectotype now a synonym of Trichoptria oogaster (Thomson, 1858) tetratoma Kieffer, 1911 (Diapria (Tropidopria)), Lectotype; syn. n. of Trichopria hyalipennis (Thomson, 1858) variipes Kieffer, 1911 (Diapria (Tropidopria)), Lectotype now a synonym of Trichopria aequata (Thomson, 1858) donisthorpei Kieffer, 1913 (Loxotropa), Lectotype now a synonym of Trichopria nigricornis (Marshall, 1868) laticeps Kieffer, 1911 (Loxotropa), Lectotype; syn. n. of Trichopria nigricornis (Marshall, 1868) morleii Chitty in Morley, 1931 (Loxotropa), syn. n. of Trichopria halterata (Kieffer, 1909 subterranea Kieffer, 1911 (Loxotropa nigricornis var.), Lectotype now a synonym of Trichopria nigricornis (Marshall, 1834) longiclava Masi, 1931 (Phaenopria), syn. n. of Trichopria fucicola (Walker, 1834) minima Masi, 1931 (Phaenopria), Lectotype; syn. n. of Trichopria cameroni (Kieffer, 1909) miron Nixon, 1980 (Phaenopria), syn. n. of Trichopria fucicola (Walker, 1834) elegans Jurine, 1807 (Psilus), Lectotype now a synonym of Trichopria verticillata (Latreille, 1804) donisthorpei Kieffer, 1911 (Tetramopria), Lectotype now a synonym of Tetramopria cincticollis Wasmann, 1899 femoralis Kieffer, 1912 (Tetramopria), Lectotype now a synonym of Tetramopria cincticollis Wasmann, 1899 alifera Nixon, 1980 (Trichopria), syn. n. of Trichopria incrassata (Jansson, 1955) atricornis Kieffer, 1911 (Trichopria), syn. n. of Trichopria halterata (Kieffer, 1909) bachyptera Maneval, 1937 (Trichopria), syn. n. of Trichopria halterata (Kieffer, 1909) balli Maneval, 1937 (Trichopria), syn. n. of Trichopria halterata (Kieffer, 1909) cameroni Kieffer, 1909 (Trichopria), Lectotype described as Phaenopria cameroni ciliaris Kieffer, 1911 (Trichopria), Lectotype; syn. n. of Trichopria basalis (Thomson, 1858) conotoma (Kieffer, 1911) (Trichopria), Lectotype described as Diapria (Tropidopria) conotoma debauchei Wall, 1980 (Trichopria), syn. n. of Trichopria prema Nixon, 1980 elegans Priesner, 1940 (Trichopria), syn. n. of Viennopria lacustris (Schulz, 1910) fimbriata Kieffer, 1911 (Trichopria), Lectotype; syn. n. of Trichopria nigra (Nees, 1834) formicaria Kieffer, 1911 (Trichopria), Lectotype now a synonym of Trichopria sociabilis Masner, 1965 halterata (Kieffer, 1909) (Trichopria), Lectotype described as Phaenopria halterata hyalinipennis (Thomson, 1858) (Trichopria), Lectotype described as Diapria hyalinipennis incrassata (Jansson, 1955) (Trichopria), Lectotype described as Phaenopria incrassata inermis Kieffer, 1909 (Trichopria), Lectotype now a synonym of Trichopria nigra (Nees, 1834) isis Nixon, 1980 (Trichopria), syn. n. of Trichopria aequata (Thomson, 1858) modesta (Ratzeburg, 1848) (Trichopria), Neotype; comb. nov. hitherto Diapria modesta morio (Thomson, 1858) (Trichopria), Lectotype described as Diapria morio natans Kieffer, 1916 (Trichopria), Lectotype; syn. n. of Viennopria lacustris (Schulz, 1910) nixoni Notton, 1995 (Trichopria), Lectotype; nom. n. pro Trichopria bifoveata Nixon, 1980, nec Ashmead, 1896 oogaster (Thomson, 1858) (Trichopria), Lectotype described as Diapria oogaster paludicola Notton, 1995 (Trichopria), nom. n. pro Trichopria nana Nixon, 1980, nec Sundholm, 1970 sequester Nixon, 1980 (Trichopria), syn. n. of Trichopria subimpressa (Kieffer, 1911) stelenes Nixon, 1980 (Trichopria), syn. n. of Trichopria credne Nixon, 1980 subimpressa (Kieffer, 1911) (Trichopria), Lectotype described as Phaenopria subimpressa suspecta (Nees, 1834) (Trichopria), Lectotype described as Diapria suspecta tenuicornis (Thomson, 1858) (Trichopria), Lectotype described as Diapria tenuicornis thomsoni Kieffer, 1911 (Trichopria), Lectotype; syn. n. of Trichopria basalis (Thomson, 1858) tritoma (Thomson, 1858) (Trichopria), Lectotype described as Diapria tritoma sociata Kieffer, 1905 (Tropidopria), syn. n. of Trichopria modesta (Ratzeburg, 1834) priesneri Jansson, 1953 (Viennopria), Lectotype now a synonym of Viennopria lacustris (Schulz, 1910)